2019
DOI: 10.1038/s41467-019-09313-8
|View full text |Cite
|
Sign up to set email alerts
|

Photon acceleration and tunable broadband harmonics generation in nonlinear time-dependent metasurfaces

Abstract: Time-dependent nonlinear media, such as rapidly generated plasmas produced via laser ionization of gases, can increase the energy of individual laser photons and generate tunable high-order harmonic pulses. This phenomenon, known as photon acceleration, has traditionally required extreme-intensity laser pulses and macroscopic propagation lengths. Here, we report on a novel nonlinear material—an ultrathin semiconductor metasurface—that exhibits efficient photon acceleration at low intensities. We observe a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 63 publications
2
84
0
Order By: Relevance
“…The photon acceleration efficiency for the third-harmonic signal was measured to be ~22%. The observed blue-shift was found to be in good agreement with a time varying photon mode amplitude model considering free carrier accumulation due to four-photon absorption process [112]. Photon acceleration based on time-varying optical processes in resonant dielectric metasurfaces presents a promising platform for performing robust pulse-shaping operations [112].…”
Section: Photon Accelerationsupporting
confidence: 57%
See 1 more Smart Citation
“…The photon acceleration efficiency for the third-harmonic signal was measured to be ~22%. The observed blue-shift was found to be in good agreement with a time varying photon mode amplitude model considering free carrier accumulation due to four-photon absorption process [112]. Photon acceleration based on time-varying optical processes in resonant dielectric metasurfaces presents a promising platform for performing robust pulse-shaping operations [112].…”
Section: Photon Accelerationsupporting
confidence: 57%
“…Such spectral shifts of light in the presence of time-varying optical processes is termed as photon acceleration and has been studied previous in plasma media [111]. Similar effect have recently been observed in silicon based resonant metasurface due to shift in the resonant wavelength with increasing incident light fluence due to time-dependent free-carrier accumulation [112]. Schematic of the silicon-rectangular structures used to study photon acceleration is shown in Figure 19a.…”
Section: Photon Accelerationmentioning
confidence: 58%
“…Note that the coefficient T 0 = 0.89 was applied to adjust the data for the residual reflectance that is not related to the properties of the metasurface. In contrast with the recently discovered blue-shifting of the entire spectrum due to the plasma driven increase of the refractive index [8], here, the spectral reshaping happens on both the red and blue sides of the TVM resonance as shown in Fig. 2(d), where extinction spectrum is color-coded as a function of the delay time.…”
Section: Scalementioning
confidence: 57%
“…The key challenge addressed by our work is finding the appropriate photonic platofrm for entering this new regime without producing large numbers of FCs that can blue-shift 32 Here, we design and fabricate an ultrathin (≈ /10, where = 3.95 μm) photonic platform for enhanced HHGa resonant metasurfacebased on a transparent, high-index, wide-bandgap semiconductor: gallium phosphide (GaP) [33][34][35] . The combination of high refractive index ( ≈ 3) and mid-infrared (MIR) transparency enables highly localized "hot spots" of the electromagnetic field inside GaP-based metasurfaces, akin to those made of silicon and gallium arsenide 36,37 .…”
Section: The Resonantly Enhanced Conversion Efficiency Facilitates Simentioning
confidence: 99%